La mer et l’insistance paradoxale dans quelques poèmes de G. M. Hopkins - Gildas Lemardelé (Revue LISA)
The impact of the sea in G. M. Hopkins’s poems cannot be overlooked, if only because of the pivotal role it plays in his most famous poem “The Wreck of the Deutschland”. Other poems however, display maritime or water-related elements that are fraught with significance. In Hopkins’s poetry, the sea is thus essentially and intricately linked to poetical, philosophical or theological tenets. When he resorts to the sea imagery, violence and benevolence are intertwined, but this binary stance is ultimately subsumed in what can be defined as an illustration of divine insistence as a fundamentally paradoxical principle, which in turn informs the poet’s personal spiritual experience.